Crystal structures and fluorescence properties of two architecture-correlated Zn(II)/Cd(II) MOFs constructed from an unprecedented tri-triazole ligand. Issue 5 (3rd April 2019) - Zhang, Yan; Shi, Dong-Wei; Ma, Yu-Qi; Li, Hai-Ye; Bian, He-Dong; Liu, Han-Fu; Tang, Jie; Huang, Fu-Ping
Abstract: By employing an unprecedented tri-triazole ligand, 4-amino-3, 5-bis-(1H-1, 2, 4-triazole)-1, 2, 4-triazole (H2 L), two Zn(II)/Cd(II) metal-organic frameworks (MOFs), [ZnL]·3H2 O (1 ) and [CdL]·H2 O (2 ), were successfully synthesized and characterized. In the two complexes, M(II) centers are chelated and bridged by L bridges to form a one-dimensional (1-D) 41 helical chain in1 with high-symmetry Pbca, and a 21 helical chain in2 with lower symmetry P 21 /n, respectively. The two chains are further linked by L into two structure-correlated three-dimensional (3-D) architectures. PXRD and TG analysis confirmed the phase purity and stability of1 and2 . The solid-state fluorescence properties of the prepared MOF revealed a maximum emission at 382 nm and 393 nm ( λ ex = 330 nm), ascribing to the intra-ligand transitions. Interestingly, an additional strong emission peak at 516 nm can be observed in1 (below 400 °C), while the emission was silenced in2 . The additional emission band may be attributed to the subtle difference of architectural features and coordination configurations between in1 and2 . Abstract :